Menakar Relevansi Pemikiran Ali Yafie dalam Perbankan Syariah dari Konsep ke Realitas - Kurnia Nur Aliffia; Lutfiyah; Ariibah Radita Ayu Candrika; Miss Fatihah Saman (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research reviews the relevance of Ali Yafie's thoughts in Islamic banking, considering that he is one of the many figures who contributed to the development of the economy in Indonesia. This research aims to know and understand what are the main points or ideas of Ali Yafie's thoughts in contributing to Islamic banking and to know the relevance of these thoughts today. This research study was explored using descriptive qualitative methods. The results show that the concept of Islamic banking promoted by Ali Yafie is still very relevant and has been implemented in Islamic banking practices in Indonesia. His thoughts emphasize the importance of justice, partnership, and mutual welfare in sharia-based economic activities not just profitability. although not yet as a whole, because there are some things that have not been perfectly realized in practice, Ali Yafie's thoughts have been able to prove that his thoughts are relevant and also direct the implementation of Islamic banking in Indonesia to remain based on sharia principles.